HUBUNGAN KOORDINASI MATA KAKI DENGAN AKURASI PASSING PEMAIN SEPAKBOLA DSKM DURI - Muhammad Irfan; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the results of the researchers' observations in the field at DSKM Duri display there are several weaknesses that appear along with the occurrence of the players in doing exercises and in soccer matches, namely the lack of maximum in passing. The purpose of this study was to find out about the relationship of eye and foot coordination with the passing accuracy of DSKM Duri soccer game. The type of research was carried out using correlations and as for the population in this study all objects of research, namely DSKM soccer players consisting of 18 people. From the results obtained, it can be concluded that eye and foot coordination has a significant relationship with the accuracy of passing in soccer games in DSKM Duri athletes. This can be seen from the results of the analysis obtained namely r count (0.908)> r table (0.482) at α = 0.05. Key Words: Eye and Foot Coordination, Passing Accuracy